The Existence of The Indonesia Peatland Restoration Agency in Perspective of Organization and Authority - Sri Nurhari Susanto; Kadek Cahya Susila Wibawa (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
The Indonesia Peatland Restoration Agency (BRGI) is established with the legal basis of Presidential Regulation Number 1 Year 2016. BRGI is founded by coordinating and facilitating peatland restoration in several regions in Indonesia. BRGI is a non-structural institution which is under responsible to the President. BRGI is a state's auxiliary organ (agency or supporting / supporting body). In authority, BRGI can expand its tasks and functions given by the Presidential Regulation or outside the Article 2 and 3 of Presidential Regulation No. 1 2016. Article 30 section (1) clearly states that BRG conducts the duties for 5 (five) years and ends on December 31st, 2020. This is further strengthened by the provision of Article 31 which states that the Presidential Regulation is valid for five years from the enactment. The President with his prerogative has the authority whether to continue the existence of the BRGI or not, even though the Presidential Regulation clearly states the expiration of the institution. Keyword: The Indonesia Peatland Restoration Agency (BRGI), authority, prerogative. Abstrak Badan Restorasi Lahan Gambut Indonesia (BRGI) didirikan dengan dasar hukum Peraturan Presiden Nomor 1 Tahun 2016. BRGI didirikan dengan mengoordinasi dan memfasilitasi restorasi lahan gambut di beberapa daerah di Indonesia. BRGI adalah lembaga non-struktural yang bertanggung jawab kepada Presiden. BRGI adalah organ bantu negara (lembaga atau badan pendukung / pendukung). Dalam wewenangnya, BRGI dapat memperluas tugas dan fungsinya yang diberikan oleh Peraturan Presiden atau di luar Pasal 2 dan 3 Peraturan Presiden No. 1 2016. Pasal 30 ayat (1) dengan jelas menyatakan bahwa BRG melaksanakan tugas selama 5 (lima) tahun dan berakhir pada tanggal 31 Desember 2020. Hal ini semakin diperkuat dengan ketentuan Pasal 31 yang menyatakan bahwa Peraturan Presiden ini berlaku selama lima tahun sejak berlakunya. Presiden dengan hak prerogatifnya memiliki wewenang apakah akan melanjutkan keberadaan BRGI atau tidak, meskipun Peraturan Presiden dengan jelas menyatakan berakhirnya lembaga. Kata kunci: Badan Restorasi Lahan Gambut Indonesia (BRGI), otoritas, hak prerogatif.